Repensando um modelo de classificação dos jogos esportivos - uma proposta inicial - Canan, Felipe (Educación Física y Ciencia.)
Considering the growing creation and diffusion of sports games -many of them quite peculiar- this text was aimed to carry out an exercise of theoretical revision of the classifications that seek to group the sports games taking into account aspects related to their respective internal logic. This paper was a theoretical research that, apart from presenting a discussion about the concept of sport and sports games and the accomplishment of an inventory of these games, adopted as a point of reflection the analysis of some sports games that present a particular character. The need of conjugation and adjustments in the existing classifications was noticed, such as modifying some nomenclatures and adding some categories and subcategories of sports games.